COVID-19 Antibody Levels among Various Vaccination Groups, One-Year Antibody Follow-Up in Two University Hospitals from Western and Central Turkey - Mehmet Soylu; Pınar Sağıroğlu; Muhammed Alper Özarslan; Oğuzhan Acet; Zeynep Türe Yüce; Feyza İzci Çetinkaya; Seyfi Durmaz; Ömür Mustafa Parkan; Deniz Akyol; Ayşin Zeytinoğlu; Gamze Kalın Ünüvar; Meltem Taşbakan; et al. (Vaccines, 2024)
Various clinical outcomes, reinfections, vaccination programs, and antibody responses resulted from the COVID-19 pandemic. This study investigated the time-dependent changes in SARS-CoV-2 antibody responses in infected and/or vaccinated and unvaccinated individuals and to provide insights into spike and nucleocapsid antibodies, which fluctuate during infectious and non-infectious states. This cohort study was carried out at the Ege University Faculty of Medicine hospital in İzmir (western Turkey) and the Erciyes University Faculty of Medicine hospital in Kayseri (central Turkey) between December 2021 and January 2023, which coincided with the second half of COVID-19 pandemic. The study included 100 COVID-19 PCR-positive patients and 190 healthcare workers (HCWs). Antibody levels were followed up via quantitative anti-SARS-CoV-2 spike and qualitative anti-nucleocapsid immunoassays (Elecsys™). Antibody levels declined after infection but persisted for at least 6–8 months. Individuals who had received only CoronaVac had higher anti-nucleocapsid antibody levels in the early months than those who received mixed vaccination. However, anti-spike antibodies persisted longer and at higher levels in individuals who had received mixed vaccinations. This suggests that combining two different vaccine platforms may provide a synergistic effect, resulting in more durable and broad-spectrum immunity against SARS-CoV-2. The study provides information about the vaccination and antibody status of healthcare workers in the second half of the pandemic and provides valuable insights into the dynamics of antibody responses to COVID-19 infection and vaccination.